Modifying BSC for national nanotechnology development: an implication for “social capital” role in NIS theory - Ghazinoory, Sepehr; Soofi, Abdol (Technological and Economic Development of Economy, 2012)
In this research, we have designed and implemented the Strategy Map and Balanced Scorecard technique in evaluating the progress of National Iranian Nanotechnology Initiative (NINI). In conducting this research, we have learned that the layers of Strategy Map are congruent with the National Innovation System (NIS) levels. The use of Strategy Map and Balanced Scorecard in conjunction with an opinion survey of the nanotechnology experts showed “social capital” at the bottom layer and economic development at the top layer of the Strategy Map of the NIS infrastructure in Iran. These findings have broad implications not only for Iranian nanotechnology development, but also are important for the theory of NIS.